Nikolay Gogol’s Story “A Bewitched Place”: An Attempt at Reading - Vladislav Sh. Krivonos (Достоевский и мировая культура: Филологический журнал)
The article offers a philological reading of Gogol’s “A Bewitched Place.” The aim of the proposed approach is to examine features of its artistic structure that remain understudied in Gogol scholarship and require special consideration. Hence the attention to the title of the story, which derives from the name of the locus — both plotwise and semantically tied to Dikanka as the primary setting. The text of the story is marked by its spatial quality, “Dikansky,” where the key event that determines its specificity is the clash of a human with the demonic sphere. The author interprets the title as a self-designation of Gogol’s spatial text, centered on the paradigm of the bewitched place. This semiotically charged spatial point functions as an opening into an unreal world inhabited by evil spirits, from which demonic influences that have captured the hero emanate. They lead to his temporary corruption, as he succumbs to the temptation of quick enrichment. The “devilish force,” as the narrator calls it, lures and seduces the hero, aiming not to destroy but to fool and mock him. It manipulates his perception, through optical and acoustic illusions, and appears to succeed. However, because of this trial, the hero discovers a readiness and determination to resist devil temptations in the future, should he encounter them again. This underscores the story’s significance as the concluding piece of the cycle, casting a retrospective light on the preceding tales.